2019
DOI: 10.3748/wjg.v25.i38.5800
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 alleviates endoplasmic reticulum stress-mediated apoptosis of intestinal epithelial cells in ulcerative colitis

Abstract: BACKGROUNDSirtuin 1 (SIRT1) is a nicotinamide adenine dinucleotide (NAD+)-dependent protein deacetylase that is involved in various diseases, including cancers, metabolic diseases, and inflammation-associated diseases. However, the role of SIRT1 in ulcerative colitis (UC) is still confusing.AIMTo investigate the role of SIRT1 in intestinal epithelial cells (IECs) in UC and further explore the underlying mechanisms.METHODSWe developed a coculture model using macrophages and Caco-2 cells. After treatment with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…[10][11][12] SIRT1 is activated in many central nervous system diseases, such as subarachnoid haemorrhage and Parkinson's disease. 13 In addition, it has been reported that it is an important…”
mentioning
confidence: 99%
“…[10][11][12] SIRT1 is activated in many central nervous system diseases, such as subarachnoid haemorrhage and Parkinson's disease. 13 In addition, it has been reported that it is an important…”
mentioning
confidence: 99%
“…SRT1720 is a strong SIRT1 activator that has been used in a variety of experimental studies [ 30 ]. The anti-inflammatory and anti-apoptotic effects of SRT1720 have been observed both in vivo and in vitro [ 31 , 32 ]. In the present study, we found that treatment with the SIRT1 activator SRT1720 significantly alleviated LPS/D-Gal-induced fulminant hepatitis and improved the survival rate of the experimental animals, suggesting that SRT1720 might have potential value for the control of fulminant hepatitis, a life-threatening condition.…”
Section: Discussionmentioning
confidence: 99%
“…CHOP is a key molecule in the downstream of PERK, and ER stress can be mediated by the PERK-CHOP pathway [11]. Caspase-12 is another marker of ER stress which is cleaved into active fragment on ER stress [22].The augment of these ER stress markers is considered to correlate with increased calcium level and directly destroys the balance of calcium homeostasis which is another important characteristic of AD [5,12,16]. Results in our study showed the decrease in the expression of GRP78, CHOP and cleaved caspase-12 after treatment of schisandrin which indicated the positive effect of schisandrin on ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 has been reported to relieve the ER stress and inflammation [1]. It is demonstrated that SIRT1 may alleviate the ER stress-regulated apoptosis via the decreased expression of CHOP and inactivation of caspase-12 [22]. Moreover, SIRT1 suppresses the ER stress through the mediation of eIF2α deacetylation [20].…”
Section: Discussionmentioning
confidence: 99%